Modulation of Biofilm Exopolysaccharides by the Streptococcus mutans vicX Gene - Lei, Lei; Yang, Yingming; Mao, Mengying; Li, Hong; Li, Meng; Yang, Yan; Yin, Jiaxin; Hu, Tao (Frontiers in Microbiology, 2015)
The cariogenic pathogen Streptococcus mutans effectively utilizes dietary sucrose for the synthesis of exopolysaccharide, which act as a scaffold for its biofilm, thus contributing to its pathogenicity, environmental stress tolerance, and antimicrobial resistance. The two-component system VicRK of S. mutans regulates a group of virulence genes that are associated with biofilm matrix synthesis. Knockout of vicX affects biofilm formation, oxidative stress tolerance, and transformation of S. mutans. However, little is known regarding the vicX-modulated structural characteristics of the exopolysaccharides underlying the biofilm formation and the phenotypes of the vicX mutants. Here, we identified the role of vicX in the structural characteristics of the exopolysaccharide matrix and biofilm physiology. The vicX mutant (SmuvicX) biofilms seemingly exhibited “desertification” with architecturally impaired exopolysaccharide-enmeshed cell clusters, compared with the UA159 strain (S. mutans wild type strain). Concomitantly, SmuvicX showed a decrease in water-insoluble glucan (WIG) synthesis and in WIG/water-soluble glucan (WSG) ratio. Gel permeation chromatography (GPC) showed that the WIG isolated from the SmuvicX biofilms had a much lower molecular weight compared with the UA159 strain indicating differences in polysaccharide chain lengths. A monosaccharide composition analysis demonstrated the importance of the vicX gene in the glucose metabolism. We performed metabolite profiling via 1H nuclear magnetic resonance spectroscopy, which showed that several chemical shifts were absent in both WSG and WIG of SmuvicX biofilms compared with the UA159 strain. Thus, the modulation of structural characteristics of exopolysaccharide by vicX provides new insights into the interaction between the exopolysaccharide structure, gene functions, and cariogenicity. Our results suggest that vicX gene modulates the structural characteristics of exopolysaccharide associated with cariogenicity, which may be explored as a potential target that contributes to dental caries management. Furthermore, the methods used to purify the EPS of S. mutans biofilms and to analyze multiple aspects of its structure (gel permeation chromatography, gas chromatography-mass spectrometry, and 1H nuclear magnetic resonance spectroscopy) may be useful approaches to determine the roles of other virulence genes for dental caries prevention.